The Algebra of a q-Analogue of Multiple Harmonic Series - Takeyama, Y. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We introduce an algebra which describes the multiplication structure of a family of q-series containing a q-analogue of multiple zeta values. The double shuffle relations are formulated in our framework. They contain a q-analogue of Hoffman's identity for multiple zeta values. We also discuss the dimension of the space spanned by the linear relations realized in our algebra.